2012
DOI: 10.1029/2012gl052232
|View full text |Cite
|
Sign up to set email alerts
|

Aquarius reveals salinity structure of tropical instability waves

Abstract: Sea surface salinity (SSS) measurements from the Aquarius/SAC‐D satellite during September–December 2011 provide the first satellite observations of the salinity structure of tropical instability waves (TIWs) in the Pacific. The related SSS anomaly has a magnitude of approximately ±0.5 PSU. Different from sea surface temperature (SST) and sea surface height anomaly (SSHA) where TIW‐related propagating signals are stronger a few degrees away from the equator, the SSS signature of TIWs is largest near the equato… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

12
116
0

Year Published

2014
2014
2014
2014

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 130 publications
(128 citation statements)
references
References 41 publications
(62 reference statements)
12
116
0
Order By: Relevance
“…TIWs have been detected in the atmospheric boundary layer and modulations of ocean surface wind stress as observed by scatterometers [Liu et al, 2000;Polito et al, 2001;Yu and Liu, 2003]. The TIW pattern is also identifiable in chlorophyll a (chl a) [Strutton et al, 2001;McClain et al, 2002;Lee et al, 2012].…”
Section: Introductionmentioning
confidence: 81%
See 2 more Smart Citations
“…TIWs have been detected in the atmospheric boundary layer and modulations of ocean surface wind stress as observed by scatterometers [Liu et al, 2000;Polito et al, 2001;Yu and Liu, 2003]. The TIW pattern is also identifiable in chlorophyll a (chl a) [Strutton et al, 2001;McClain et al, 2002;Lee et al, 2012].…”
Section: Introductionmentioning
confidence: 81%
“…The spatial and temporal variabilities of ocean surface salinity in the tropical eastern and central Pacific Ocean are poorly known mostly because in situ salinity observations are sparse. With the advent of satellite salinity measurements, it is now possible to analyze the salinity signal associated with TIWs [Lee et al, 2012]. This provides a significant new capability to the scope of TIW observations that has important implications to ocean circulation and climate [Lagerloef, 2008].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Aquarius, launched in June 2011, has been providing SSS measurements since September 2011 with 7 day global coverage. Lee et al [2012] demonstrated the advantage of Aquarius' SSS in improving the understanding of Pacific TIWs. In particular, Aquarius SSS data captured the dominant 17 day TIWs near the equator that were not well observed by SST and SSH.…”
Section: Key Pointsmentioning
confidence: 95%
“…Thousand kilometer zonal scale propagating waves with typical periods of tens of days have been observed in the tropical Pacific and Atlantic Oceans, affecting the physical and biogeochemical properties of the ocean and its interaction with the atmosphere [e.g., Legeckis, 1977;Legeckis and Reverdin, 1983;McPhaden et al, 1984;Hayes et al, 1989;Luther and Johnson, 1990;Yoder et al, 1994;Qiao and Weisberg, 1995;McPhaden, 1996;Xie et al, 1998;Chelton et al, 2000;Liu et al, 2000;Polito et al, 2001;Lee et al, 2012]. These tropical instability waves (TIWs) are generated from barotropic and baroclinic instabilities associated with the horizontal and vertical shear of equatorial current systems and related density gradients [e.g., Philander, 1978;Weisberg and Weingartner, 1988;McCreary and Yu, 1992;Masina et al, 1999;Grodsky et al, 2005;Jochum et al, 2004;Lyman et al, 2007;von Schuckmann et al, 2008].…”
Section: Introductionmentioning
confidence: 99%